Implementasi Green Economy melalui Pelatihan Pengolahan Beras Menir Menjadi Susu Beras di Desa Pematang Johar - Pesta Gultom; Desma Erica Maryati Manik; Elisabeth Nainggolan; Irvan Rolyesh Situmorang (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
One of the MSMEs in Pematang Johar village is agriculture. Rice yields are abundant, with the potential to produce approximately 12,250 tons per harvest season. This harvest undergoes a post-harvest process that ultimately produces rice, and the remaining rice milling residue becomes rice grits. The goal of this Community Service Program (PKM) activity is to utilize the rice grits from the rice milling process to create a nutritious and economically valuable rice milk product for the agripreneur community. The PKM activity utilizes the Participatory Action Research (PAR) method, positioning the agripreneur community in Pematang Johar village not only as objects but also as active subjects or partners. The results of this activity have a positive impact, reducing crop waste, making it more useful and improving the well-being of the Pematang Johar community.